Expressions of miR-21 and miR-210 in Breast Cancer and Their Predictive Values for Prognosis - Xiaofei WU (Tehran University of Medical Sciences, 2020)
Background: We aimed to investigate the expressions of miR-21 and miR-210 in the breast cancer tissue and their correlation with clinicopathological features and prognosis. Methods: A retrospective analysis was performed on 68 patients with breast cancer treated surgically in Wuhan General Hospital of Guangzhou Military in 2014-2015. The breast cancer tissue and the adjacent normal tissue were collected from the patients. Quantitative real-time PCR (qRT-PCR) was used to detect the expression levels of miR-21 and miR-210 in the breast cancer and adjacent normal tissues. Results: According to qRT-PCR, the expression levels of miR-210 and miR-21 in the breast cancer tissue were significantly higher than those in the adjacent normal tissue (P<0.05), which were significantly correlated with lymph node metastasis, clinical staging and differentiation of patients (P<0.05). miR-21 and miR-210 were significantly positive correlated in both breast cancer tissues and adjacent normal tissues (r=0.7014, 0.7502, P<0.001). The survival rate in the miR-210 high expression group was significantly lower than that in the miR-210 low expression group (P<0.05), whereas there was no significant difference between the miR-21 high and low expression groups. Conclusion: miR-21 and miR-210 are highly expressed in the breast cancer tissue and significantly correlated with lymph node metastasis, clinical staging and differentiation. miR-210, the up-regulated expression of which is related to the poor prognosis of patients with breast cancer, may be a potential prognostic indicator for breast cancer, which can be used to judge the prognosis.